Back Cover: Regiocomplementary O‐Methylation of Catechols by Using Three‐Enzyme Cascades (ChemBioChem 18/2015). Issue 18 (December 2015) - Siegrist, Jutta; Aschwanden, Simon; Mordhorst, Silja; Thöny‐Meyer, Linda; Richter, Michael; Andexer, Jennifer N.
Abstract : The back cover picture shows the three‐enzyme cascade for regiocomplementary O‐methylation of catechols. This cascade can be imagined as a jigsaw puzzle containing exchangeable pieces. The methyltransferase reaction is integrated in a cascade with an S‐adenosylmethionine‐generating methionine adenosyltransferase (cofactor supply) and a methylthioadenosine‐S‐adenosylhomocysteine nucleosidase (by‐product degradation). This system allows the combination of various enzymes and substrates. As a proof of concept, two regiocomplementary catechol‐O‐methyltransferases, which catalyse the reaction towards meta ‐ or para ‐methylated catechols, were applied. Both methyltransferases show a broad substrate range and give rise to a variety of building blocks.